Leadership agility developing your repertoire of leadership styles - Ron Meyer and Ronald Meijers (Abingdon, Oxon ; New York, NY Routledge, Taylor & Francis Group, 2018)
Leadership is about influencing others to move in a certain direction and there are many ways of achieving this influence. Each of these leadership styles has its inherent qualities and pitfalls, and will be more suited to specific people and different circumstances. The more leaders understand their preferred leadership styles and are able to flexibly switch to the most suitable style given the situation, the more effective they will be. This book maps out ten sets of opposite leadership styles, giving readers the possibility to understand the strengths and weaknesses of both sides, and to identify their own current preference.
Includes bibliographical references and index.
Keywords: Leadership